Vascular Endothelial Growth Factor Concentrations in Dogs with Spirocercosis. (6th September 2013) - Mukorera, V.; Kirberger, R.M.; Mabeta, P.; Dvir, E.
<x xml:space="preserve">Abstract</x> Background Vascular endothelial growth factor (VEGF) is a potent proangiogenic factor associated with tumor development. Spirocerca lupi is a nematode of canids that induces an esophageal nodule that progresses to a sarcoma in 25% of cases. Determination of neoplastic transformation is challenging and usually based on endoscopy‐guided biopsies under general anesthesia, an expensive procedure that often yields nondiagnostic, necrotic samples. Hypothesis Circulatory VEGF concentrations are increased in dogs with neoplastic spirocercosis and can distinguish between dogs with neoplastic and nonneoplastic disease. Animals A total of 24 client‐owned dogs, 9 nonneoplastic, 9 neoplastic, and 6 controls. Methods Case‐control study. Plasma and serum VEGF concentrations at the time of diagnosis were compared with those of healthy controls. Measurement of VEGF was performed using a canine‐specific ELISA. Kruskal‐Wallis and Dunn's tests were used for statistical analysis with significance set at P < .05. Results The median plasma VEGF concentrations of dogs with neoplastic spirocercosis were 629 pg/mL (range, 282–2, 366) higher than both the nonneoplastic (<39.5 pg/mL; range, <39.5–716) and control dogs (<39.5 pg/mL; all values, <39.5; P = .0003). The median serum VEGF concentration of the neoplastic dogs was 69 pg/mL (range, <39.5–212) higher than the nonneoplastic (<39.5 pg/mL; range, <39.5–44.13) and control dogs (<39.5 pg/mL; all values, <39.5; P = .001). Conclusions and Clinical Importance Both plasma and serum VEGF concentrations can be used to differentiate nonneoplastic and neoplastic spirocercosis. The role of VEGF in neoplastic transformation of S. lupi‐induced nodules and the potential utility of anti‐VEGF drugs in spirocercosis‐induced sarcoma warrant further investigation.